Demand Theory of Sharia Micro Economic Perspective - Ririn Makrifah; Miftahur Rahman (Journal of Islamic Economic Scholar, 2022)
The purpose of writing this article is to find out about the theory of demand in sharia microeconomics and what is related to the discussion of the theory of microeconomic demand. Economics is a human act as a consumer to fulfill needs and desires or make various requests for various goods and services in everyday life. Islamic economics itself is never separated from moral and religious values because every activity is always associated with the Shari'a. Islamic economics is the knowledge and application of sharia law to prevent injustice in the use and disposal of material resources with the aim of providing human satisfaction and carrying out these activities as an obligation to Allah and society. The Qur'an calls the economy the term istishad (saving, economy) which literally means "middle" or "moderate". Therefore, as Muslims we must take a moderate stance in acquiring and using resources. A Muslim is not allowed to be stingy (royal, exaggerating) nor is he allowed to be stingy (bakhl). The view of Islamic economics regarding demand is almost the same as conventional economics, but there are limitations for individuals to behave economically in accordance with sharia rules. In Islamic economics, "Islamic" norms and morals, which are Islamic principles in economics, are a determining factor for an individual or society in carrying out their economic activities. Therefore, Islamic economic theory is different from conventional economic theory